Учитель в языковой картине мира студентов педагогики частной школы - Iwan, Krystyna (Wydawnictwo Naukowe UAM, 2013)
This paper is based on associative research and its main objective is to define the concept of a teacher as perceived by pedagogy students. The paper shows that, in these students’ linguistic picture of the world, the concept of a teacher is mainly associated with a teacher’s moral and practical competence, whereas technical competence appears less frequently.
The concept of a teacher in the linguistic picture of the world of pedagogy students in private higher education institutions
Nauczyciel w językowym obrazie świata studentów pedagogiki szkoły niepublicznej